Langkah Awal Literasi Keuangan, Gerakan Uang Jajan Menjadi Tabungan - Malik, Ernawati; Sujana, I Wayan; Ridzal, Nining Asniar; Sidi, Mahmur (Universitas Muhammadiyah Mataram, 2026)
Abstract: Financial literacy from an early age is still low, even though it is very important to develop children's ability to manage money. Therefore, financial literacy activities were carried out at SD Negeri 48 Buton, Barangka Village, Kapontori District, to foster the habit of saving, managing pocket money, and understanding financial management from elementary school. The purpose of this activity is to increase students' awareness of matters related to money and in turn will contribute to the formation of positive character and habits in everyday life. The implementation method was carried out using lectures, discussions, simulations and the provision of piggy banks as a form of motivation for students. From the results of the quiz given after the activity, it was known that the level of student understanding of the concept of saving, students' interest in saving and saving habits from an early age with an average score of 86%. The role and cooperation of the school, teachers, parents and the environment were very helpful in motivating and supporting the sustainability of the pocket money movement program into savings.Abstrak: Literasi keuangan sejak usia dini masih rendah, padahal sangat penting untuk membentuk kemampuan anak dalam mengelola uang. Oleh karena itu, dilakukan kegiatan literasi keuangan di SD Negeri 48 Buton, Desa Barangka, Kecamatan Kapontori, guna menumbuhkan kebiasaan menabung, mengatur uang jajan, dan memahami pengelolaan keuangan sejak sekolah dasar.Tujuan kegiatan ini adalah untuk meningkatkan kesadaran siswa tentang hal-hal yang berkaitan dengan uang dan pada gilirannya akan berkontribusi pada pembentukan karakter dan kebiasaan positif dalam kehidupan sehari hari. Metode pelaksanaan dilakukan dengan metode ceramah, diskusi, simulasi dan pemberian celengan sebagai bentuk motivasi bagi siswa-siswi. Dari hasil quis yang diberikan setelah kegiatam diketahui, tingkat pemahaman siswa terhadap konsep menabung, Minat siswa terhadap menabung dan kebiasaan menabung sejak dini dengan nilai rata-rata pemahaman siswa sebesar 86%. Peran dan kerjasama pihak sekolah, guru serta orang tua dan lingkungan sangat membantu dalam memotivasi dan mendukung keberlanjutan program gerakan uang jajan menjadi tabungan.